Physical punishment in childhood: the rights of the child - Saunders, Bernadette J. (John Wiley-Blackwell, 2010)
Introduction -- Childhood and physical punishment in historical perspective -- Legal responses to physical punishment -- Conducting sensitive and ethical research with children and adults -- Experiences of physical punishment at home, at school and in public places -- Public and professional perceptions of the effectiveness of physical punishment -- The subjugation of children through language and physical punishment -- The effects of physical punishment -- The persistence of physical punishment -- The morality of physical punishment -- An idea childhood